2019
DOI: 10.1101/668848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perlin Noise Generation of Physiologically Realistic Patterns of Fibrosis

Abstract: Fibrosis, the pathological excess of fibroblast activity, is a significant health issue that hinders the function of many organs in the body, in some cases fatally. However, the severity of fibrosis-derived conditions depends on both the positioning of fibrotic affliction, and the microscopic patterning of fibroblast-deposited matrix proteins within afflicted regions. Variability in an individual's manifestation of a type of fibrosis is an important factor in explaining differences in symptoms, optimum treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Tissue simulations showed that not only could the myofibroblast infiltration affect the arrhythmia vulnerability [ 73 , 74 ], but also the fibrosis pattern can play a role in the initiation and maintenance of reentrant activity [ 46 , 47 , 54 , 75 ]. Sridhar et al [ 76 ] have shown the role that fibroblast infiltration plays regarding the onset of arrhythmia due to the increase of anisotropy in the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue simulations showed that not only could the myofibroblast infiltration affect the arrhythmia vulnerability [ 73 , 74 ], but also the fibrosis pattern can play a role in the initiation and maintenance of reentrant activity [ 46 , 47 , 54 , 75 ]. Sridhar et al [ 76 ] have shown the role that fibroblast infiltration plays regarding the onset of arrhythmia due to the increase of anisotropy in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue simulations were carried in a patch of 50 mm × 50 mm × 3 mm with a central fibrotic area (radius 10 mm) featuring 11 different fibrosis patterns. The patterns were generated as Perlin noise [ 54 ], which is used in computer-generated imagery to generate realistic textures [ 55 ]. These textures were used to distribute the myofibroblasts following the fibrotic patterns (Figure 5) observed in MRI and histological cuts from interstitial and patchy fibrotic tissue [ 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown the importance of the texture of the fibrotic tissue for excitation propagation in the cardiac substrate (Jakes et al, 2019 ; Dokuchaev et al, 2020 ; Nezlobinsky et al, 2020 ). Our proposed model aims at reproducing the deposited collagen fibers observed in tissue samples with interstitial fibrosis (Hansen et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown the importance of the texture of the fibrotic tissue for excitation propagation in the cardiac substrate [52][53][54] . Our proposed model aims at reproducing the deposited collagen fibers observed in tissue samples with interstitial fibrosis 55 .…”
Section: Fibrosis Modelingmentioning
confidence: 99%